Implementing a skill development program among food handlers in tertiary care hospital to improve their personal hygiene: A pilot study - Sudip Bhattacharya; Shweta Talati; Anil Kumar Gupta; Sunita Malhotra; Amarjeet Singh (Wolters Kluwer Medknow Publications, 2019)
INTRODUCTION: Food handlers with poor personal hygiene and lack of awareness in preventing foodborne diseases working in hospitality sectors or hospitals could spread foodborne infections. OBJECTIVE: Our study objective was to ascertain the impact of a video-based educational intervention program and administrative measures on improvement in personal hygiene of food handlers in hospital. METHODOLOGY: We conducted this pilot study among all 103 food handlers who were working in a tertiary care hospital. A checklist-based scoring and physical examination were conducted by the investigator for the food handlers. After baseline scoring S1, intervention 1 and 2 was implemented, and score was obtained as S2 and S3, respectively. Descriptive statistics was calculated, and score was compared by repeated measures ANOVA test using SPSS-22 software. RESULTS: Our study revealed that a total of 19.2% of food handlers had health complaints. More than half (54.8%) admitted that they had suffered from any kind of illness since last 6 months. Common illness was viral fever (40.3%) followed by typhoid (5.7%), dengue (4.8%) and urinary tract infection (3.8%). Most of the food handlers had long hair (62.5%) followed by long nail (57.69%). Nearly, one-fifth (20.1%) of food handlers nail was infected with fungus. Worm was found in 14.4% cases by stool examination. Statistically significant (P < 0.05) improvement in score was observed after each intervention. DISCUSSION: Poor hygiene (Score-1 = 23.76) was observed at baseline study although there was a mechanism in place for a yearly health checkup and regular (6 monthly) hygiene training. After interventions (video-based training and administrative measures), the score was improved to Score-3 (42.57). Statistically significant (P < 0.05) differences in hygiene score were observed for variables such as state of residence, education level, and working experiences (inside or outside the hospital). CONCLUSION: It is possible to improve personal hygiene among food handlers using video-based interactive training methods and administrative measures with no extra or minimal cost. RECOMMENDATIONS: This "piggyback" approach of training can be imparted in addition to routine training measures among the food handlers for improving their personal hygiene in the hospital setting.